2018
DOI: 10.1158/1078-0432.ccr-17-2032
|View full text |Cite
|
Sign up to set email alerts
|

Novel Targeting of Transcription and Metabolism in Glioblastoma

Abstract: Purpose: Glioblastoma (GBM) is highly resistant to treatment, largely due to disease heterogeneity and resistance mechanisms. We sought to investigate a promising drug that can inhibit multiple aspects of cancer cell survival mechanisms and become an effective therapeutic for GBM patients.Experimental Design: To investigate TG02, an agent with known penetration of the blood-brain barrier, we examined the effects as single agent and in combination with temozolomide, a commonly used chemotherapy in GBM. We used … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 35 publications
4
64
1
Order By: Relevance
“…These observations indicate that – theoretically – tumors sensitive to TG02 may not easily develop efficient escape strategies in vivo . Our study complements and extends another recent study exploring the activity of TG02 in different glioma models in vitro and in vivo that focused on synergy with TMZ and changes in energy metabolism . These authors confirmed CDK9 as the main target of TG02 and hypothesized that mitochondrial dysfunction and ATP depletion were the proximate cause of cell death, consistent with our assumption that caspase inhibition delays cell death, but that cell death induced by TG02 can proceed in a caspase‐independent manner.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…These observations indicate that – theoretically – tumors sensitive to TG02 may not easily develop efficient escape strategies in vivo . Our study complements and extends another recent study exploring the activity of TG02 in different glioma models in vitro and in vivo that focused on synergy with TMZ and changes in energy metabolism . These authors confirmed CDK9 as the main target of TG02 and hypothesized that mitochondrial dysfunction and ATP depletion were the proximate cause of cell death, consistent with our assumption that caspase inhibition delays cell death, but that cell death induced by TG02 can proceed in a caspase‐independent manner.…”
Section: Discussionsupporting
confidence: 89%
“…TG02 and hypothesized that mitochondrial dysfunction and ATP depletion were the proximate cause of cell death, consistent with our assumption that caspase inhibition delays cell death, but that cell death induced by TG02 can proceed in a caspaseindependent manner. While Su et al observed no activity of TG02 alone in the GL-261 mouse glioma model, 32 we observed moderate single agent activity in two human glioma models, including one GIC model ( Figs. 1g and 1h).…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…Over-expression of both MGMT and APNG have been linked to resistance to alkylating agents, and are associated with lower survival rates in patients [10,11], while MGMT methylation (a mark of reduced average expression) has been linked to improved survival. Consequently, it has been hypothesized that MGMT and APNG expression or methylation may be used as biomarkers for glioma response to treatment with alkylating agents such as TMZ [12,13,14].…”
Section: Introductionmentioning
confidence: 99%